The Importance of Race in Teak, Tectona grandis L. - Beard, J. S. (Indian Forester, 1943)
Teak has been raised in Trinidad from seed imported both from India and Burma. There are marked differences between the quality of the two strains, and vegetative differences which divide them into separate "races". In Java several distinct races of teak are recognised and trials have shown those from Burma and Siam to be the best. Those who wish to introduce teak in tropical America should be careful as to the source of their seed